Archival Material Conservation : Strategies and Challenges/সংরক্ষণাগারের উপকরণ সংরক্ষণের সুপরিকল্পিত কর্মপদ্ধতি ও প্রতিকূলতা সমূহ (TRISANGAM INTERNATIONAL REFEREED JOURNAL, 2025)
The preservation of archival material is a critical responsibility for libraries, archives, and cultural institutions, ensuring that historical records remain accessible for future generations. Preservation strategies encompass both preventive and curative measures, including environmental control, digitization, proper storage, disaster preparedness, and the use of conservation treatments. The shift towards preservation has introduced new opportunities for access and longevity, but it also raises concerns related to technology obsolescence, metadata standards, and sustainability of digital repositories. Despite advancements, significant challenges persist – such as limited funding, inadequate infrastructure, lack of skilled professionals, and the deterioration of fragile or rare materials due to environmental and human factors. Addressing these issues requires a balanced approach that combines traditional conservation methods with modern digital technologies, alongside strong policy frameworks and collaborative efforts. Ultimately, successful preservation depends on continuous innovation, capacity building, and institutional commitment to safeguarding cultural heritage.
Keywords: Archival materials; Knowledge; Deterioration; Preservation; Conservation; Strategies; Challenges